Electrodeposited Cu2ZnSnS4 thin films - Valdes, Matias Hernan (2013)
Cu2ZnSnS4 (CZTS) thin films have been prepared using Electrochemical Atomic Layer Deposition (EC-ALD and also by one-step conventional constant potential electrodeposition. Optimal deposition conditions were investigated using cyclic voltammetry (CV). Then, based on CVs results, CZTS films were grown employing EC-ALD deposition cycles using the sequence Au/S/Cu/S/Zn/S/Sn/S to form the desired quaternary compound. In parallel, conventional one-step electrodeposition was carried out at -0.85 V vs. Ag/AgCl over 1 hour. A thermal treatment in sulfur vapor was also investigated in an attempt to optimize the stoichiometry. The crystal structure of the films was characterized by XRD and micro Raman spectroscopy, while the morphology, thickness, topography and elemental composition were investigated using FIB-SEM and EDS.